Using Genes to Explore the Relationship of Cognitive and Non-cognitive Skills with Education and Labor Market Outcomes - Thomas Buser; Rafael Ahlskog; Magnus Johannesson; Philipp Koellinger; Sven Oskarsson (Institute of Labor Economics (IZA), 2023)
A large literature establishes that cognitive and non-cognitive skills are strongly correlated with educational attainment and professional achievement. Isolating the causal effects of these traits on career outcomes is made difficult by reverse causality and selection issues. We suggest a different approach: instead of using direct measures of individual traits, we use differences between individuals in the presence of genetic variants that are associated with differences in skills and personality traits. Genes are fixed over the life cycle and genetic differences between full siblings are random, making it possible to establish the causal effects of within-family genetic variation. We link genetic data from individuals in the Swedish Twin Registry to government registry data and find evidence for causal effects of genetic differences linked to cognitive skills, personality traits, and economic preferences on professional achievement and educational attainment. Our results also demonstrate that education and labor market outcomes are partially the result of a genetic lottery.
Keywords: J24; D91; I26; 330; personality traits; economic preferences; cognitive skills; labor markets; education; polygenic indices